The Elements of Harmony and Lexical Fitting in the Poem”“Not Compromising” by the poet“Amal Dunqul (مجلة إحالات, 2026)
The research falls within the framework of linguistic work, which uses among the procedures of textual analysis the lexical and semantic structure as a means of understanding the textual content and uncovering its depths, in search of semantic structures that form the spaces of the text.